Biofilm formation by persistent and non-persistent listeria monocytogenes strains on abiotic surfaces - Magalhães, R. (2017)
Contaminated food with Listeria monocytogenes is the predominant route of transmission of listeriosis to humans, a severe illness with a high mortality rate. Food processing environments can be colonized by persistent strains, repeatedly isolated for months or years. This study aimed to investigate the biofilm formation capacity of six strains of L. monocytogenes that persisted for long periods in two cheese processing plants in comparison to seven strains isolated sporadically from the same plants. Persistent strains produced more biofilm than non-persistent strains on stainless steel and silicon rubber surfaces; no significant differences were observed on polyvinyl chloride (PVC). In a polystyrene microtiter plate assay with crystal violet staining, no evidence was found that persistent strains have higher ability to form biofilm than non-persistent strains, and no correlation was identified between biofilm formation in the microtiter plate and on the three other surfaces tested.